Leishmaniasis in Sri Lanka: Surmounting obstacles toward achieving elimination as a public health problem by 2028 - Shalindra Ranasinghe; Deepika Fernando; Nayana Gunathilaka; Kanchana Mallawaarachchi; Rajitha Wickremasinghe (Annals of Medical Science and Research)
In the 1990s, Sri Lanka started reporting cases of cutaneous leishmaniasis (CL), which gradually increased to the current case incidence rate of over 3000/year. The causative strain of CL is Leishmania donovani MON-37, which is genetically different from the visceral leishmaniasis (VL)-causing strain in Sri Lanka. Visceral and mucosal forms are rare in Sri Lanka. The potential vector is Phlebotomus argentipes. Due to increasing CL case numbers, the Anti-Malaria Campaign was identified as the focal point in 2022 by the Ministry of Health (MoH) to control leishmaniasis and a WHO-funded situational analysis and the first National Strategic Plan (NSP) for prevention and control of leishmaniasis in Sri Lanka 2024–2028 were developed. During the situational analysis, a comprehensive literature review, meeting the stakeholders, visiting CL endemic areas and hospitals, and a SWOT analysis were carried out. The goal of the NSP is “To control cutaneous leishmaniasis for possible elimination as a public health problem in the future and prevention of VL and MCL.” The two objectives are as follows: to reduce the annual incidence of CL < 5 per 10,000 population by 2028 (approximately 6600 cases) and to ensure zero mortality due to VL. The NSP had three strategic plans and five supporting areas. Each activity was well-described, and timelines were given to complete each task. This review describes the activities carried out by the MoH, the research work conducted so far, and the key points in the NSP recommended to eliminate leishmaniasis as a public health problem from Sri Lanka by 2028.